Aldoximes are precursors of auxins in Arabidopsis and maize. Issue 4 (10th June 2021) - Perez, Veronica C.; Dai, Ru; Bai, Bing; Tomiczek, Breanna; Askey, Bryce C.; Zhang, Yi; Rubin, Garret M.; Ding, Yousong; Grenning, Alexander; Block, Anna K.; Kim, Jeongim
Summary: Two natural auxins, phenylacetic acid (PAA) and indole‐3‐acetic acid (IAA), play crucial roles in plant growth and development. One route of IAA biosynthesis uses the glucosinolate intermediate indole‐3‐acetaldoxime (IAOx) as a precursor, which is thought to occur only in glucosinolate‐producing plants in Brassicales. A recent study showed that overproducing phenylacetaldoxime (PAOx) in Arabidopsis increases PAA production. However, it remains unknown whether this increased PAA resulted from hydrolysis of PAOx‐derived benzyl glucosinolate or, like IAOx‐derived IAA, is directly converted from PAOx. If glucosinolate hydrolysis is not required, aldoxime‐derived auxin biosynthesis may occur beyond Brassicales. To better understand aldoxime‐derived auxin biosynthesis, we conducted an isotope‐labelled aldoxime feeding assay using an Arabidopsis glucosinolate‐deficient mutant sur1 and maize, and transcriptomics analysis. Our study demonstrated that the conversion of PAOx to PAA does not require glucosinolates in Arabidopsis. Furthermore, maize produces PAA and IAA from PAOx and IAOx, respectively, indicating that aldoxime‐derived auxin biosynthesis also occurs in maize. Considering that aldoxime production occurs widely in the plant kingdom, aldoxime‐derived auxin biosynthesis is likely to be more widespread than originally believed. A genome‐wide transcriptomics study using PAOx‐overproduction plants identified complex metabolic networks among IAA, PAA, phenylpropanoid and tryptophan metabolism.